Remittances and the Dutch disease - Pablo A. Acosta; Emmanuel K. K. Lartey; Federico S. Mandelman (Federal Reserve Bank of Atlanta, 2009)
Using data for El Salvador and Bayesian techniques, we develop and estimate a two-sector dynamic stochastic general equilibrium model to analyze the effects of remittances in emerging market economies. We find that, whether altruistically motivated or otherwise, an increase in remittance flows leads to a decline in labor supply and an increase in consumption demand that is biased toward nontradables. The higher nontradable prices serve as incentive for an expansion of that sector, culminating in reallocation of labor away from the tradable sector; a phenomenon known as the Dutch disease. Quantitative results also indicate that remittances improve households'welfare as they smooth income flows and increase consumption and leisure levels. A Bayesian vector autoregression analysis provides results that are consistent with the dynamics of the model.
Keywords: F40; F41; O10; 330; Dutch disease; real exchange rate; remittances; Rücküberweisung (Migranten); Dutch Disease; Kaufkraftparität; Theorie; El Salvador